“THE PSYCHOLOGICAL EFFECTS OF SOCIAL MEDIA PLATFORM USE ON ADOLESCENT” (International Journal of Food and Nutritional Sciences, 2022)
Social media platform is becoming a bigger part of teenagers' everyday life, which has sparked a lot of research on the psychological effects of this use. The goal of this study is to perform a comprehensive analysis of the intricate connection between teenage social media platform use and psychological well-being. This study attempts to elucidate the complex changes in social media platform on adolescents' emotional and cognitive development through an interdisciplinary approach involving digital communication studies, psychology, and sociology. The first part of the study looks at the motivations behind teen social media platform use. Determining the underlying causes of usage patterns lays the foundation for deciphering the psychological effects that follow